Estimating The Prevalence of Non-Communicable Diseases and Adherence to Dietary Habits And Physical Activity Among Healthcare Professionals in The Middle East And North Africa Regions - Abdelhalim, Nada; Eltewacy, Nael Kamel; Owais, Tarek A.; Salman, Saif; Hamza, Nouran; Islam, Sheikh Mohammed Shariful; Collaborators, EARG (Journal of Current Health Sciences, 2024)
The rising number of fatalities linked to food, exercise, and non-communicable illnesses has sparked interest in studying their effects. In society, Healthcare Professionals (HCPs) symbolize health and wellbeing. However, the incidence of chronic illness and healthy habits among Middle East and North Africa (MENA) HCPs remains unclear. To determine the prevalence of chronic diseases and adherence to healthy dietary habits and physical activity among HCPs in the MENA region. Algeria, Egypt, El Yemen, Iraq, Jordan, Kuwait, Libya, Palestine, Saudi Arabia, Sudan, and Syria HCPs (physicians, dentists, nurses, pharmacists, and nutritionists) participated in multicenter cross-sectional research. April to June 2022 data on diet and exercise habits was collected using a pre-tested self-administered questionnaire. Demographics, risk factors, medical history, and nutrition and exercise were included in the questionnaire. HCP diet and exercise were examined using multivariable regression models. A study of 7130 HCPs (mean age 28.6 ± 7.8 years, 57.5% females) was conducted. Physicians held 56.8% of the sample population, followed by pharmacists, nurses, dentists, and nutritionists. Cardiovascular disease (CVD) affected 33.1% of individuals. Alcohol, pork, soda, sugar, and smoking raised the risk of non-communicable diseases. Nutritionists were the most active HCPs. About half of dietitians (45.3%) walked 150 minutes or more per week, while 14.7% and 25.9% did 150 minutes or more of moderate and 75 minutes or more of intense exercise, respectively. HCPs in MENA had high rates of CVD and risk factors such smoking, alcohol, pork, soda, sugar, and less exercise. MENA HCPs must be aware of the significant incidence of these risk factors to enhance health behavior.